2017
DOI: 10.1371/journal.pone.0170435
|View full text |Cite
|
Sign up to set email alerts
|

Radioiodinated Exendin-4 Is Superior to the Radiometal-Labelled Glucagon-Like Peptide-1 Receptor Probes Overcoming Their High Kidney Uptake

Abstract: GLP-1 receptors are ideal targets for preoperative imaging of benign insulinoma and for quantifying the beta cell mass. The existing clinical tracers targeting GLP-1R are all agonists with low specific activity and very high kidney uptake. In order to solve those issues we evaluated GLP-1R agonist Ex-4 and antagonist Ex(9–39) radioiodinated at Tyr40 side by side with [Nle14,Lys40(Ahx-DOTA-68Ga)NH2]Ex-4 (68Ga-Ex-4) used in the clinic. The Kd, Bmax, internalization and binding kinetics of [Nle14,125I-Tyr40-NH2]E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 33 publications
1
17
1
Order By: Relevance
“…A surprising finding is the lower pancreas uptake of [ 125 I]Exendin-4 in our study in comparison with another 125 I-labeled Exendin-4 reported by Läppchen et al [ 32 ]. This group have successfully labeled Exendin-4 with 125 I, and the uptake of the tracer, [Nle 14 , 125 I-Tyr 40 -NH 2 ]Ex-4, in the pancreas was 25.3 ± 4.2%IA/g at the same 1-h time point [ 32 ]. It is important to mention that Exendin-4 was labeled using two different methods in these studies.…”
Section: Discussioncontrasting
confidence: 65%
“…A surprising finding is the lower pancreas uptake of [ 125 I]Exendin-4 in our study in comparison with another 125 I-labeled Exendin-4 reported by Läppchen et al [ 32 ]. This group have successfully labeled Exendin-4 with 125 I, and the uptake of the tracer, [Nle 14 , 125 I-Tyr 40 -NH 2 ]Ex-4, in the pancreas was 25.3 ± 4.2%IA/g at the same 1-h time point [ 32 ]. It is important to mention that Exendin-4 was labeled using two different methods in these studies.…”
Section: Discussioncontrasting
confidence: 65%
“…All cell experiments were performed in a human embryonic kidney HEK-293 cell line stably expressing human sst2 receptors (HEK-hsst2) (a gift from Prof. Schulz, University of Jena) plated in 6-well plates in triplicates (10 6 cells/well). The saturation binding experiments were performed with radioligand ( 64/nat Cu-NODAGA-JR11 and 64/nat Cu-DOTA-TATE) concentrations ranging from 0.5–75 nM and 0.5–90 nM, respectively, for 2 hours at +4ºC as described previously [ 24 ]. The K d and Bmax values were calculated using GraphPad.…”
Section: Methodsmentioning
confidence: 99%
“…For both indium‐111 and technetium‐99m exendin‐based tracers, tumor‐to‐kidney ratios do increase over time, and therefore, authors suggest that additional late scans should be made in case of negative scans early after injection, as has been suggested for longer‐lived positron‐emitting radionuclides such as zirconium‐89 as well . The use of radioiodinated exendin‐based tracers should also be considered to reduce renal accumulation …”
Section: Imaging Of Insulinoma With Exendin‐4–based Tracersmentioning
confidence: 99%
“…[ 125 I]I‐BH‐exendin(9‐39) exhibited high uptake in murine pancreas, and the antagonist [Lys 27 ( 125 I]I‐BH‐exendin(9‐39)NH 2 demonstrated tumor uptake that was comparable with the agonists but with a substantially reduced kidney uptake . In contrast, the antagonist [Nle 14 ,[ 125 I]I‐Tyr 40 ‐NH 2 ]exendin(9‐39) showed lower affinity and lower internalization than the more favorable agonist [Nle 14 ,[ 125 I]I‐Tyr 40 ‐NH 2 ]exendin‐4 …”
Section: Imaging Of Insulinoma With Exendin‐4–based Tracersmentioning
confidence: 99%